Modelling of catalytic cracking taking into account the catalyst deactivation by coke and heavy metals; Chemical Reactors (CHEMREACTOR-23) - Nazarova G. Yu. Galina Yurievna; Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Shafran T. A. Tatjyana Aleksandrovna (2018, 2018)
Title screen